STUDI PERBANDINGAN KETEPATAN SASARAN SMASH ANTARA UMPAN SENDIRI DAN DI UMPAN OLEH TEMAN DALAM PERMAINAN SEPAK TAKRAW REGU PUTRI KABUPATEN SUMBAWA TAHUN 2017/2018 - Sri Dahliah; Maulidin Maulidin; Nurdin Nurdin (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2018)
The purpose of this study is to find out there is comparison of smash accuracy on target between self ball feeding and teammate ball feeding in female sepak takraw in Sumbawa in 2017/2018. The ability to feed in the smash is important because without being able to feed well and direct the ball on the attacker, a score would not be reached. The smash technique can be performed in two ways; feeding the ball by a player himself and feeding the ball by a teammate who will perform the smash then. The formulation of the problem in this research is stated as whether or not there is comparison study of smash accuracy on target between self ball feeding and teammate ball feeding in female sepak takraw in Sumbawa in 2017/2018. The sample used in this study amounted to 20 players and divided into 2 groups of sampling techniques using purposive sampling. The data analysis used statistical analysis with t-test formula. The results of this hypothesis test analysis shows that the t-score is higher than t-table whereas t-score 3.670 > t-table 2.101 at 5% significance level which means that the null hypothesis is rejected while the alternative hypothesis is accepted. It can be concluded that there is comparison of target smash accuracy on self ball feeding and teammate ball feeding in female sepak takraw game in Sumbawa District in 2017/2018.